Studies on solvent precipitation of levan synthesized using Bacillus subtilis MTCC 441 - Jothi Sailaja C.A. Chidambaram (Heliyon, 2019)
Levan is a water soluble biopolymer widely used in food, pharma, personal care and aquaculture industries. In this work, levan was synthesized by Bacillus subtilis MTCC 441 using sucrose as a sole carbon source. Effects of pH, sucrose concentration, nitrogen source, nitrogen concentration, inoculum size and agitation speed on levan production were studied. Yeast extract (YE) was found to be the best nitrogen source. Sucrose concentration – 100 g/L, pH – 7, YE concentration – 2 g/L, inoculum size 10% (v/v) and RPM – 150 were found to be optimal values for levan production. Effects of precipitation pH (3–12), choice of solvent (ethanol, isopropanol, acetone, and methanol) and supernatant to solvent ratio (1:1 to 1:6) on levan yield were also studied. Isopropanol resulted in maximum levan recovery among the four solvents considered. Optimal pH and supernatant to solvent ratio for levan precipitation were found to be 11 and 1:5, respectively. Corresponding levan yield was 0.395 g/g of sucrose supplied. The product obtained was characterized using FTIR, 1H-NMR, 13C-NMR, and GPC. The cytotoxicity of the precipitated levan was studied on EA.hy926 cell line using MTT assay and the compound was proven to be non-toxic to the cells.